Comparison of seizure characteristics in full term neonates with stroke and hypoxic ischemic encephalopathy. (4th April 2011) - Lynch, N; Low, E; Rennie, J; Boylan, G
Abstract : Aims: Up to 20% of neonatal seizures are secondary to perinatal stroke. Diagnosis relies largely on neuroimaging which is often delayed. The aim of this study was to describe the clinical and electrographic characteristics of seizures in full term newborns with perinatal stroke and to compare them with seizures due to hypoxic ischemic encephalopathy (HIE). Methods: Continuous multichannel EEG recordings of ≥24 h in neonates with evidence of stroke or HIE were reviewed. Electrographic seizures were annotated and defined as sudden repetitive stereotyped discharges lasting for at least 10 s on at least one EEG channel. Background EEG grade, seizure duration, frequency, location and morphology were measured. The median seizure duration and overall seizure burden were also measured. Results: Six term neonates were identified with MRI or CT confirmation of unilateral stroke in arterial distribution between 2003 and 2010. The EEGs of these babies were compared with those of 14 term neonates, born during the same period, with HIE. Neonates with stroke had a mean seizure burden of 161 min whereas infants with HIE had a mean seizure burden of 351 min. Infants in the stroke group had a mean number of 49 seizures versus a mean of 112 seizures in the HIE group. Background EEG in infants with stroke showed continuous mixed frequency activity with evidence of sleep cycling over the unaffected side. All neonates in the HIE group showed background abnormalities consistent with grade 2 or 3 HIE and sleep cycling was absent. All seizures in stroke cases were focal and accompanied by clonic seizures prior to AED administration. Seizures also showed a characteristic spike or polyspike morphology over the affected side in contrast to a predominantly diffuse sharp wave morphology in HIE. Conclusions: This is the first study to compare long term multi channel EEGs obtained from neonates with a subsequent confirmed diagnosis of stroke, with EEG from neonates with HIE. It has identified clear differences between the EEG background activity and electrographic seizures in neonates with stroke and HIE which may aid diagnosis in the early newborn period.